Implementasi Kebijakan Desa Siaga Dalam Meningkatkan Perilaku Hidup Bersih dan Sehat di Kecamatan Tapa Kabupaten Bone Bolango - Adian Syafruddin Ibrahim (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik (J-EMSPOL), 2024)
This research was conducted in the District Tapa Bolango Bone regency, with the aim of this study was to determine and analyze the Alert Village Policy Implementation in Developing Clean and Healthy Behavior in District Tapa Bone Bolango District and the factors inhibiting. The analytical method used in this research is descriptive analysis method with a qualitative approach, and use interartive models. The method of data collecting in this research is observation, interview and documentation. The results showed that the implementation of policy such as government support, community support and socialization influence on the Clean and Healthy Lifestyle (PHBS).  In realizing the implementation, the are several oftacles including a lack of health personnel, finanncing, infrastructure and society cultural factors. Therefore, the government is expected to provide policy support in increase the budget, improving health infrastructure and actively participate in the disemination of public awarness of the importence of a clean and healthy lifestyle.